PERBANDINGAN KEBIJAKAN DIMENSI SMART PEOPLE DALAM PERWUJUDAN SMART CITY DI KOTA METROPOLITAN: Dimension Policy of Smart People in Metropolitan City of Bandung, Jakarta, and Pekanbaru - Baskoro Wicaksono; Refaldo Asta; M. Rafi (Research and Development Agency Ministry of Home Affairs, 2021)
The advancement of information and communication technology (ICT) has become a major focus that is often seen in Indonesia's concept of smart cities. As a result, various stakeholders often ignore smart people's dimensions, which have an essential role in realizing a smart city. Therefore, this study aims to explain and compare various smart people policies in metropolitan cities such as Bandung, Jakarta, and Pekanbaru. This study uses literature study research techniques sourced from journals, proceedings, books, and official government websites that provide information relevant to the study's focus. The results showed that smart people's policy dimensions in Bandung, Jakarta, and Pekanbaru consist of three policy dimensions: policies at the education level, creative industry policies, and Smart City Living Lab policies. In the education sector policy, the Municipal Governments of Bandung, Jakarta, and Pekanbaru have the same program orientation. Then, the creative industry sector policy has a different program orientation. The city of Bandung focuses on developing the Little Bandung website, Jakarta focuses on the One District One Center (OK OCE) program. In contrast, Pekanbaru focuses on the Madani Food Week program. Furthermore, the policies in the Smart City Living Lab sector in Bandung, Jakarta, and Pekanbaru have not focused on the parameters of the small-scale smart city development model.